2006
DOI: 10.3402/ijch.v65i5.18146
|View full text |Cite
|
Sign up to set email alerts
|

Youth and adult community member beliefs about Inupiat youth suicide and its prevention.

Abstract: Objectives. To better understand youth and adult community members' perceived causes and possible preventative steps to address the high Inupiat youth suicide rates in Northwest Alaska. Study Design. A five-item, open-ended survey focusing on community members' perceptions of suicide causes, warning signs, and protective factors was administered in the twelve Native villages served by the Maniilaq Association, a native non-profit organization. Methods. A total of 382 surveys were completed. Qualitative answers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 15 publications
1
45
0
1
Order By: Relevance
“…Despite the long held belief by researchers and indigenous peoples alike of the positive relationship between traditional culture and mental well-being (Johnson & Tomren, 1999;Kirmayer et al, 2000;Strickland, Walsh, & Cooper, 2006;Wexler & Goodwin, 2006;Wolsko, Lardon, Hopkins, & Ruppert, 2006), the topic has not been extensively studied quantitatively. With regard to suicide, Chandler and colleagues have found that those FN communities in B.C.…”
Section: Substance Usementioning
confidence: 99%
“…Despite the long held belief by researchers and indigenous peoples alike of the positive relationship between traditional culture and mental well-being (Johnson & Tomren, 1999;Kirmayer et al, 2000;Strickland, Walsh, & Cooper, 2006;Wexler & Goodwin, 2006;Wolsko, Lardon, Hopkins, & Ruppert, 2006), the topic has not been extensively studied quantitatively. With regard to suicide, Chandler and colleagues have found that those FN communities in B.C.…”
Section: Substance Usementioning
confidence: 99%
“…Communication and interaction within one's family and community are known protective factors (Mohatt et al, 2004;Wexler and Goodwin, 2006;Kral et al, 2011); whether this protective nature extends to communication and interaction between communities is less clear, but it may be likely. For example, in an adaptation context, despite great variability across northern communities with respect to the changes being experienced, the existing challenges faced, and the ways in which people can best adapt, there is still much that can be learned from one another about best practices in adaptation (Ford and Pearce, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These known protective factors are synonymous with key characteristics of strong adaptive capacity. For example, connecting youth with older community members is not only a factor well established as important for circumpolar Indigenous youth resilience (Kirmayer et al, 1998;Wexler and Goodwin, 2006;Kral et al, 2011;DeCou et al, 2013;Wexler et al, 2013Wexler et al, , 2014, but also an essential aspect of sharing traditional knowledge between generations, which, in turn, can increase adaptive capacity to respond to climate change impacts and climate-related challenges (Ford et al, 2006Pearce et al, 2011). Thus, protective factors play an important role in building youth resilience and adaptive capacities within circumpolar Indigenous populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The project, which builds on findings from several community-based research projects, [12][13] began in 2006 and is funded by the Substance Abuse and Mental Health Services Administration.…”
Section: Referral To Gun Locker and Locking Medicine Cabinets For At mentioning
confidence: 99%